TRANSFORMASI PAJAK DIGITAL DAN TANTANGAN - Permatasari, Desi; Putri, Tsania Rahma; Marcelina, Voni (Neraca: Jurnal Ekonomi, Manajemen dan Akuntansi, 2023)
Digital transactions are non-cash payments such as mobile banking or other virtual transaction devices. Digital transactions are a form of reform in the world of taxation, which is a form of tax payment or imposition of value added tax (VAT) on digital products or internet business products.